Smart Cities, Smart Citizens? Imagined users in a data driven environment. - Pöchhacker, Nikolaus Helge (My University, 2016)
Smart Cities repräsentieren (scheinbar) ein neues Paradigma innerhalb der Stadtplanung und städtischen Entwicklungen, welches oft als seine neue Dimension der Integration von IKT in die städtische Umgebung diskutiert wird. Im Zuge dessen werden Smart Cities oft als rein technologische Unternehmungen, mit dem Ziel urbane Prozesse durch digitale Mittel zu optimieren, verstanden. Das Konzept der Smart City ist jedoch kontingent und subsumiert eine große Bandbreite von Ideen, Werten und Visionen unter diesem Begriff. Es gibt nicht die eine Smart City, stattdessen stellt die tatsächlich anzutreffende Smart City eine Übersetzung dieser sehr allgemein gehaltenen Vision von Stadtplanung in den jeweiligen lokalen Kontext dar. Die Arbeit erforscht die Smart City Initiative der Stadt Wien und wie diese den Smart Citizen in Bezug auf die formulierten Ziele und Visionen der zukünftigen Smart City Wien konstruiert. Auf der empirischen Ebene wird der Smart Citizen durch die Analyse von offiziellen Dokumenten und Strategien mit Bezug zur Smart City Wien, Interviews mit wichtigen Akteuren und Beobachtungen von Partizipationsveranstaltungen innerhalb Wiens sowie von neu gebauten Stadtteilen als die Materialisierung der Smart City Vision zusammen gesetzt. Die Ergebnisse der Studie legen nahe, dass der Smart Citizen als ein individualistisches, kompetentes und verantwortungsvolles Mitglied der Smart City Gemeinschaft konstruiert wird. Durch Prozesse der Responsibilisierung basiert die Smart City Wien zu einem hohen Grad auf freiwillige Verhaltensänderungen und einem Smart City Bewusstsein seiner Bewohner. Eine wichtige Ressource für diese geänderten Praktiken und Wertsysteme ist eine prävalente und allgemein geteilte Form des Wissens. Dieses Wissen ermöglicht jedem Individuum abzuleiten, was es bedeutet ein Smart Citizen zu sein.

Smart cities (seemingly) represent new paradigm of urban development, which is often discussed as a whole new dimension of the integration of ICT in the urban environment. Smart cities therefore are often understood as mainly technological endeavours, aiming at optimising urban processes with digital means. However, the notion of the smart city is highly contingent and a wide variety of ideas, values and imaginaries are subsumed under this term. There is no such thing as the one smart city. The actual smart city is a translation of this more general vision on urban planning into local contexts. As a result every local translation of a smart city emphasises different aspects, adds new meanings to the term or tries to subvert the original meaning completely. These translations of the smart city concept often take place in municipal governments and the offices of official urban planners. Their plans and ideas regarding the development of the smart city are integral parts of defining social life and social order within the imagined smart city. At the same time these imaginaries construct what one could call a smart citizen. Urban planning in general, and the smart city in particular, are constructing a certain image of its future residents, assuming characteristics and formulating demands. Starting from that observation, this thesis explores the smart city initiative of Vienna and how it constructs this smart citizen in relation to the formulated goals and visions of the future Smart City Wien. The search for Vienna s smart citizen engages thereby in the discursive construction of the imagined residents and her/his characteristics per se, but also explores the imagined and partly already realised instruments of governance to actively create a smart population. To do so, the analysis relies on the theoretical concepts of co-production and socio-technical imaginaries. Empirically, the smart citizen was re-assembled in this study by bringing together official documents and strategies regarding the Smart City Wien, interviews with stakeholders and observations from participation events taking place in Vienna and from newly built city quarters as a materialisation of the smart city imaginary. The result of this thesis suggests that the smart citizen is constructed as an individualistic, competent and responsible member of the smart city community. Through processes of responsibilisation, the Smart City Wien is heavily based on voluntary changes in practices and a smart city consciousness of its residents. The major recourse for this changed practices and values is a prevalent and commonly shared form of knowledge, from which each individual can derive, what it means to be a smart citizen. To stabilise the discursive construction of the smart citizen within Vienna s population, the city administration utilises different instruments to actively shape and (re-)produce this knowledge and to establish a specific vision of the smart city - the Smart City Wien imaginary.
Keywords: Stadtplanung; Stadtentwicklungsplanung; Interaktion; Innovation; Technologieeinsatz; Leitbild; Kooperation; Partizipation; Sozialinnovation; Digitalisierung; Smart City; Vision; Urban Governance; Transformation; Konzeption; Vernetzung; Stadtentwicklungspolitik; Bürgerbeteiligung